2020
DOI: 10.22190/fupes200530027s
|View full text |Cite
|
Sign up to set email alerts
|

Razlike U Motoričkim Kompetencijama Dece Mlađeg Školskog Uzrasta

Abstract: The aim of this study was to examine the differences in motor competence among children of different school ages, as well as whether there is a negative trend in the decline of these values with increased age. The research was conducted in a school environment, the sample consisted of 151 male and female children, age 7-11 years, divided into four approximately equal subsamples: first grade children N=36 (7.4±0.3 years, Mean±SD), second grade children N=41 (8.5±0.3 years, Mean±SD), third grade children N=40 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The test items were taken from a well-validated test battery (DKT) [5]. A major advantage of the test items selected is their high comparability with data from other studies; all three test items can be found in studies conducted in Germany and internationally for the measurement of motor performance (6-min run, e.g., [24]; standing long jump, e.g., [23,40]; lateral jumping, e.g., [41]).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…The test items were taken from a well-validated test battery (DKT) [5]. A major advantage of the test items selected is their high comparability with data from other studies; all three test items can be found in studies conducted in Germany and internationally for the measurement of motor performance (6-min run, e.g., [24]; standing long jump, e.g., [23,40]; lateral jumping, e.g., [41]).…”
Section: Strengths and Weaknessesmentioning
confidence: 99%